Organizational Culture Towards Culture of Excellence - Manolito San Jose (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2022)
This study examined the organizational culture of the College of Education of Polytechnic University of the Philippines. An institution's organizational culture determines the faculty members' attitudes, values, characters, goals, and aspirations. It identifies their nature and how they act or perform their duties and responsibilities no matter what their position is. Adopting a positive culture in an institution produced a positive outcome, promoting success in the organization. Loyalty to the organization is one of the greatest assets of the faculty members working in the College. Unity amidst the diversity exists in the College of Education that makes the organization continue to succeed and strive for excellence. According to Edgar Schein (1985),